Ectoparasitofauna (Acari: Ixodida and Gamasida; Insecta:Siphonaptera) from terrestrial mammals: diversity, taxonomic aspects and associated zoonotic rickettsiales in Legado das Águas - Reserva Votorantim, in Tapiraí and Miracatu, São Paulo - Pesenato, Isabella Pereira (2023)
Bacteria of the Rickettsia are responsible for causing various diseases around the world and have caused major epidemics in the past. In Brazil, the spotted fever group is a serious public health concern, involving environmental and animal issues. The transmission of rickettsiae is primarily associated with ticks, but lice, mites and fleas can also be involved in the dissemination. The aim of this study was to collect the ectoparasitofauna present in a fragment of primary Atlantic Rainforest located within a private reserve (Legado das Águas - Reserva Votorantim) in the state of São Paulo, Brazil. Ticks, mites and fleas were collected from small terrestrial mammals, dogs, humans and also by observing the vegetation in its free-living stages, and blood samples were obtained from rodents, marsupials and dogs. After collection, these samples were identified and tested for bacteria of the Rickettsia genus using molecular and serological tools and culture on Vero cells. A total of 476 small terrestrial mammals, 189 bats, and 12 dogs were captured, from which 6,947 mites, 1,458 fleas and, 2,714 ticks were collected. New host-related parasitism relationships were observed, as well as new species locality records. Molecular tests revealed three species of rickettsia circulating in the tick population: Rickettsia bellii, Rickettsia parkeri strain Atlantic Rainforest and Rickettsia rhipicephali, and two isolates of R. bellii were obtained from Amblyomma ovale ticks using the viral shell technique. The serological tests were compatible with the results of the tick tests, with high titres for the three bacteria in question and only one specimen from Didelphis aurita showed titres compatible with Rickettsia amblyommatis. Flea and mite specimens were tested using the same targets, but none amplified rickettsial DNA. The results of this study provide a better understanding of the ecology of hosts, ectoparasites and bacteria of the Rickettsia genus in environmental conditions without or with little human action and how anthropogenic actions affect the distribution of these pathogens.